2020
DOI: 10.15252/emmm.202012105
|View full text |Cite
|
Sign up to set email alerts
|

Neuron type‐specific increase in lamin B1 contributes to nuclear dysfunction in Huntington’s disease

Abstract: Lamins are crucial proteins for nuclear functionality. Here, we provide new evidence showing that increased lamin B1 levels contribute to the pathophysiology of Huntington’s disease (HD), a CAG repeat‐associated neurodegenerative disorder. Through fluorescence‐activated nuclear suspension imaging, we show that nucleus from striatal medium‐sized spiny and CA1 hippocampal neurons display increased lamin B1 levels, in correlation with altered nuclear morphology and nucleocytoplasmic transport disruption. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 91 publications
8
36
1
1
Order By: Relevance
“…Aberrant nuclear architecture has been reported in several neurodegenerative disease models and our analysis of human neurones derived from different HD lines further supports the view that this is also a feature of HD (Edens et al, 2013;Frost et al, 2016;Gasset-Rosa et al, 2017;Alcalá-Vida et al, 2021). Lamin-B1 is a nuclear envelope protein that is highly expressed in neurons and provides structural support to the nucleus (Stuurman et al, 1998;Takamori et al, 2018).…”
Section: High Content Imaging Can Detect Nucleocytoplasmic Transport Phenotypes In Striatal Neuronssupporting
confidence: 85%
See 3 more Smart Citations
“…Aberrant nuclear architecture has been reported in several neurodegenerative disease models and our analysis of human neurones derived from different HD lines further supports the view that this is also a feature of HD (Edens et al, 2013;Frost et al, 2016;Gasset-Rosa et al, 2017;Alcalá-Vida et al, 2021). Lamin-B1 is a nuclear envelope protein that is highly expressed in neurons and provides structural support to the nucleus (Stuurman et al, 1998;Takamori et al, 2018).…”
Section: High Content Imaging Can Detect Nucleocytoplasmic Transport Phenotypes In Striatal Neuronssupporting
confidence: 85%
“…Reduced RANGAP1 expression was observed in HD mice at late disease stages (Grima et al, 2017), whereas we found reduced RAN and RANGAP1 protein levels in our "young" PSC-derived neurones, suggesting that nuclear pore protein reduction may be an earlier phenotype than previously indicated through its links with aggregation. Interestingly increased lamin-B1 protein expression has been described in an HD mouse model, and further overexpression of lamin-B1 resulted in morphological changes in neurons (Alcalá-Vida et al, 2021). We did not observe increased lamin-B1 expression, possibly due to lower polyQ lengths of our neurons compared to the mouse model.…”
Section: Nuclear Pore Transport Components Are Disrupted On a Transcriptional And Protein Level In Huntington's Diseasecontrasting
confidence: 40%
See 2 more Smart Citations
“…Considering (1) the functions of TCF4 in neurogenesis ( Schoof et al, 2020 ; Wang et al, 2020 ) and neural plasticity ( Kennedy et al, 2016 ; Thaxton et al, 2018 ; Badowska et al, 2020 ); (2) high expression of TCF4 in hippocampal neuroepithelium and its persistence in all mature hippocampal neuron subpopulations and astrocytes and similar high expression in cortical structures ( Jung et al, 2018 ; Kim et al, 2020 ); and (3) downregulation of TCF4 we show here in R6/1 mouse and HD patient hippocampus and cerebral cortex, allows to hypothesize that TCF4 might play a role in the impairment of cognitive functions in HD. In R6/1 mice, the motor and cognitive symptoms generally appear at 12–20 weeks of age ( Naver et al, 2003 ; Bolivar et al, 2004 ; Giralt et al, 2013 ), and treatment with papaverin (inhibitor of PDE10a) or betulinic acid improve these symptoms ( Giralt et al, 2013 ; Alcalá‐Vida et al, 2021 ). Importantly, both of these compounds affect PKA and cAMP levels, which are known to increase TCF4 transcriptional activity ( Sepp et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%